Apple genomics for the Swedish breeding programme - Skytte af Sätra, Jonas (2023)
Swedish apple (Malus domestica Borkh.) cultivation is a niche market setting specific requirements on new apple cultivars. Notably, the growing season is short, especially in central and northern Sweden, and there are relatively few pesticides available, making resistance to diseases important. The past decade has seen major developments in tools for genomics-led breeding in apple and targeted application of these tools could facilitate a major increase in efficiency. The aim of this thesis has been to lay the foundations for genomics-led breeding in the Swedish apple breeding programme. In a first step, the status of available genetic resources was investigated and curated (Paper I). A robust high-resolution virtual linkage map (Paper II) was then developed by analysis of two whole genome sequences and use of a high-density linkage map. Identification of pedigree relationships and use of a reliable map for marker ordering enabled production of highly curated and phase-resolved marker data. Apple germplasm was screened for resistance to European canker (Neonectria ditissima) and quantitative trait loci (QTL) in segregating offspring of ‘Aroma’ x ‘Discovery’ were mapped (Paper III). The metabolomic profiles of the parents during early stages of infection provided insight on the potential roles of two of the mapped QTL, and indicated that ‘Santana’ might provide a complementary source of resistance (Paper IV). The effect of previously published genomic regions and QTL intervals for date of flowering and harvest date under Nordic conditions were investigated in germplasm relevant for Nordic apple breeding (Paper V). A study on the genetic basis for adaptation to northern Sweden was initiated, with the timing of canopy senescence identified as a correlating trait (Paper VI). The applicability of the novel data obtained was illustrated by discussing future crosses that could be relevant for breeding to improve resistance to N. ditissima and adaptation to central and northern Sweden.